Changes in Diet Quality over 10 Years Are Associated with Baseline Sociodemographic and Lifestyle Factors in the Multiethnic Cohort Study. Issue 7 (27th April 2020) - Park, Song-Yi; Shvetsov, Yurii B; Kang, Minji; Setiawan, Veronica Wendy; Wilkens, Lynne R; Le Marchand, Loïc; Boushey, Carol J
ABSTRACT: Background: Trends in diet quality among US adults indicate a steady improvement, but data on longitudinal individual-level changes in diet quality are still limited. Objective: We examined changes in diet quality over 10 y and sought to determine whether baseline sociodemographic and lifestyle factors predicted the changes in a multiethnic population. Methods: Data were from 63, 255 African American, Native Hawaiian, Japanese American, Latino, and white men and women (45–75 y old at baseline) in the Multiethnic Cohort, who completed a quantitative food frequency questionnaire at baseline (1993–1996) and 10-y follow-up (2003–2007) and had no prevalent cancer or heart disease at either survey. Overall diet quality was measured by use of the Healthy Eating Index–2015 (HEI-2015), the Alternative Healthy Eating Index–2010 (AHEI-2010), the alternate Mediterranean Diet score, and the Dietary Approaches to Stop Hypertension (DASH) score. We used a general linear model with adjustment for covariates to compare diet quality changes by baseline characteristics in men and women separately. Results: Overall diet quality improved over 10 y by 3.2 points in men and 2.9 in women assessed using the HEI-2015, although scores for some components worsened (saturated and trans fats, indicating increased intake) or remained unchanged at a low quality level (whole grains, dairy, and sodium). In multivariable models where changes in HEI-2015, AHEI-2010, and DASH were harmonized to a 100-point score, greater increases in scores in both men and women were found for Japanese American ethnicity (increase by 0.5–4.7 in the 3 scores, P < 0.03), higher education (by 0.5–1.5, P  ≤ 0.001), normal weight (BMI 18.5 to <25, by 0.6–2.5, P  ≤ 0.01), nonsmoking (by 1.5–2.7, P < 0.001), higher moderate/vigorous physical activity level (by 0.3–0.8, P  ≤ 0.04), and multivitamin use (by 0.4–0.7, P < 0.001) at baseline. Conclusions: Sociodemographic and lifestyle factors, closely associated with diet quality, also predicted subsequent changes in diet quality over time in this multiethnic population.